Understanding the patient experience and treatment benefits in patients with non–small‐cell lung cancer with brain metastasis - David Cella; Patrick Y. Wen; Claire Ervin; Susan Vallow; Isabelle Gilloteau; Carla DeMuro; Margaret Mordin; Andrea Chassot Agostinho; Jennifer Dine (Cancer Medicine, 2023)
Abstract Background Despite the high prevalence of brain metastases (BM) secondary to non–small‐cell lung cancer (NSCLC) (NSCLC/BM), patients' experiences (symptoms and impacts) are not fully understood. This study sought to understand the patient experience with NSCLC/BM and identify a patient‐reported outcome (PRO) measure fit to capture the most important NSCLC/BM symptoms and impacts. Methods A targeted literature review was completed; the National Comprehensive Cancer Network (NCCN)/Functional Assessment of Cancer Therapy–Brain Symptom Index, 24‐item version (NFBrSI‐24) was identified as a relevant measure that assessed the core symptoms and impacts associated with NSCLC/BM. Qualitative interviews composed of concept elicitation and cognitive debriefing with oncologists (n = 3) and adult patients (n = 16) with NSCLC/BM were conducted to confirm the content validity and evaluate the relevance and appropriateness of the NFBrSI‐24 for this condition. Results The NSCLC/BM symptoms and impacts identified in the literature and reported by oncologists and patients were consistent and captured in the NFBrSI‐24. Study participants reported significant burden associated with the symptoms (commonly fatigue, headache) and impacts of NSCLC/BM. Participants indicated that the NFBrSI‐24 captured their most salient experiences with NSCLC/BM and that symptom improvement or a delay in progression, as measured by the NFBrSI‐24, would be meaningful. During the cognitive debriefing, participants generally indicated that the NFBrSI‐24 was comprehensive and easy to understand/answer and that it assessed symptoms they considered most important to treat. Conclusions These results suggest that the NFBrSI‐24 adequately captures an appropriate measure of NSCLC/BM symptoms and impact.